Development of the Pi Nora for Conservation According to Theories of the Creative Economy - Petcharak, Saran; Kaewset, Prarop; Jantapo, Anchalee (Journal of Liberal Arts Prince of Songkla University, 2019)
The pi nora is a wind instrument used to accompany traditional nora performances in Southern Thailand. Despite some similarities to other musical forms in Southeast Asia, this particular genre of music is different from the music in other regions of the world and the instruments reflect the local environment and the lifestyle and culture of the Southern Thai people. However, there is very little inheritance of pi nora playing methods from the older generations to the new, which is putting the continued development of the instrument at risk. The creative economy is one way to add value to the instrument and generate new economic and social benefits of inheritance. Therefore, this qualitative investigation was set up to conserve and develop pi nora. The three research objectives were 1) to explore the identity and traditional knowledge concerning the pi nora, 2) to study the current conditions and problems with inheritance and development of the pi nora and 3) to create a conservation and development model for the inheritance of the pi nora according to the principles of creative economy. Data was collected from 63 purposively selected individuals. Results show that 1) the pi nora is an instrument whose origin is closely related to spiritual beliefs, Brahmanism and Buddhist faith. The instrument helps build relationships between people in society and between humans and religion; Nevertheless, 2) there is an inheritance crisis that must be addressed; 3) in terms of the method for development of the pi nora according to the principles of the creative economy, the researchers synthesised development methods of new products and determined 5 suitable steps.